MiR-520b as a novel molecular target for suppressing stemness phenotype of head-neck cancer by inhibiting CD44 - Lu, Ya-Ching; Cheng, Ann-Joy; Lee, Li-Yu; You, Guo-Rung; Li, Yan-Liang; Chen, Hsin-Ying; Chang, Joseph T. (Scientific reports, 2017)
Cancer stem cells preferentially acquire the specific characteristics of stress tolerance and high mobility, allowing them to progress to a therapy-refractive state. To identify a critical molecule to regulate cancer stemness is indispensable to erratically cure cancer. In this study, we identified miR-520b as a novel molecular target to suppress head-neck cancer (HNC) with stemness phenotype. MiR-520b inhibited cellular migration and invasion via the mechanism of epithelial-mesenchymal transition. It also sensitized cells to therapeutic drug and irradiation. Significantly, miR-520b suppressed spheroid cell formation, as well as reduced expressions of multiple stemness regulators (Nestin, Twist, Nanog, Oct4). The CD44 molecule was identified as a direct target of miR-520b, as shown by the reverse correlative expressions, the response to miR-520 modulation, the luciferase reporter assay, and the functional rescue analyses. These cellular results were confirmed by a tumor xenograft mice study. Administration of miR-520b dramatically restrained tumorigenesis and liver colonization. Conversely, miR-520b silencing led to an acceleration of tumor growth. Taken together, our study demonstrated that miR-520b inhibits the malignancy of HNC through regulation of cancer stemness conversion by targeting CD44. MiR-520b may serve as an emerging therapeutic target that may be further developed for the intervention of refractory HNC.